Factors Influencing the Buying Behaviour of Organised Retail Consumers: A Study on Food and General Stores in Visakhapatnam - V. G., Smitha (Indian Journal of Marketing, 2012)
The growth in organized retailing has been the national trend over the last decade, with many organized retail chains developing larger stores that specialize in providing a wide selection of produce in a particular product range, lucrative pricing, one stop shopping etc. Organized retailing in India’s main cities, such as Bengaluru, Kolkata, Hyderabad, Pune and Chennai is growing rapidly, but such is the pace of change, that many smaller, three tier cities are now firmly on the radar screen of the retail sector and mall developers. Despite the tremendous potential - such as low property value, growing income levels, changing socio-economic profile, and a large percentage of young population, which promotes organized retailing, the growth of organized retailers in Visakhapatnam had been modest during the period from 2006-09. This prompted a study to establish the buying behavior of consumers from organized retailers in Visakhapatnam. Since the penetration of large format retail outlets in Visakhapatnam is less, even today, and since more and more organized retailers have opened up exclusive outlets for food and related items, the present study focuses on the purchase behavior of retail customers with respect to food items and general stores. The findings suggest that there are equal spaces for both organized and unorganized retailers in an emerging city like Visakhapatnam. The paper also examines the reasons for the gradual shift of consumers from unorganized retailers to organized retailers in certain product categories.